Insecticides Impact and Benefits of Its Use for Humanity - Eduardo Rebolledo Ranz, Ramón (IntechOpen, 2022)
This book deals with all aspects of chemical pest control, such as the different groups of insecticides and their modes of action, problems caused by insecticides to the environment, the resistance of pests to insecticides, and problems and legislation of different countries regarding the application of these products. It also addresses aspects of the problems caused by insecticides in fresh and marine water, as well as presents research methodologies and protocols.